Closed loop control of curing process using Lab VIEW (International Journal of Engineering and Computer Science, 2015)
The objective of this project is to simulate a curing process chamber found in many industry settings. Curing involves anyprocess where heat is used to catalyze or initiate chemical and molecular level structural changes in polymeric materials such asepoxies, phenolic, polyesters and silicones. The project aims to simulate the entire process of temperature control, its variationsand as to how PID controller determines its response in LabVIEW. Each set point is attained and controlled for the specifiedtime. On a waveform chart, all the important process parameters like set point, process variable and controller output are plottedusing a DAQ card to the host computer running LabVIEW